Religiusitas Remaja SMA: (Analisis Terhadap Fungsi dan Peran Pendidikan Agama Islam dalam Membentuk Kepribadian Siswa - Hadi, Mukhtar (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2017)
Educational responsibility is not just transferring knowledge but also transferring the values to the students themselves. The responsibility aims to form students in order to have a whole personality, ie a person who not only has a wide knowledge, but also has a deep spirituality. To achieve this noble goal is partially burdened to religious teachers in schools through Islamic Religious Education. At the level of Senior High School, students are required to have high morality and spirituality. Students are required to have a good religious knowledge as well as to practice the teachings of religion in daily life. This paper seeks to reveal the religiosity of high school students associated with learning of Islamic Religious Education in schools. More specifically, this research-based article seeks to express the high school religious religiosity in Metro City. Then know the effectiveness of PAI in SMA towards the formation of values of religiosity residing in student. And knowing the implementation of PAI in high school does substantively give emphasis on the internalization of religious values or limited to cognitive knowledge only religion. Based on the results of the research, it can be concluded that in terms of the level of religiosity or religious level of high school adolescents in Metro City, found the findings that 30% of them including Less religious categories, the remaining 47.50% including the category is quite Religious and 22.50% including the Religious category. While viewed from the effectiveness of the success of PAI in SMA towards the achievement of high school religusitas level found the fact that only 9% of the high school adolescents who claimed learning PAI is the main factor causing the achievement level of religiousity they feel. The remaining 45% is due to family factors, 12.5% because of their liveliness factor in Rohis. And the remaining 20% due to their intersection with mosques, madrassas and boarding schools (pondok pesantren). Overall implementation of learning PAI in SMA has been planned and implemented with reference to three aspects of learning objectives, namely coginitive, affective and psychomotor aspects. However, in the affective aspect, religious teachers are only able to assess the attitudes and behavior of students when in the classroom, while religious behavior outside the classroom or outside the school can not be known. The difficulty of PAI teachers in looking at the success rate of PAI is on the affective aspect, ie whether the religious values that have been implanted to the students can be internalized in the student's personal.